Disfonia organofuncional e queixas de distúrbios alérgicos e/ou digestivos Organic-functional dysphonia and complains off allergic and/or digestive disturbance - Carla Aparecida Cielo; Leila Susana Finger; Geise Roman-Niehues; Vanessa Panda Deuschle; Márcia do Amaral Siqueira (Revista CEFAC, 2009)
OBJETIVO: verificar a ocorrência de queixas de distúrbios alérgicos e/ou digestivos em pacientes com disfonia organofuncional, atendidos no Setor de Voz de uma clínica-escola de Fonoaudiologia. MÉTODOS: este estudo caracteriza-se como estudo de série, retrospectivo e transversal. Realizou-se uma análise de 113 prontuários de pacientes com disfonia organofuncional que apresentavam queixas de distúrbios alérgicos e/ou digestivos, na faixa etária de cinco a 76 anos, sendo 41 do sexo masculino e 72 do feminino. O procedimento estatístico utilizado foi o Teste de Hipótese para Duas Proporções. RESULTADOS: houve significante frequência de queixas de distúrbios alérgicos e digestivos associados nos pacientes dos disfonia organofuncional; entre as queixas de distúrbios alérgicos, de distúrbios digestivos, e de ambas associadas, as queixas de distúrbios alérgicos foram significantemente mais frequentes nos pacientes com disfonia organofuncional. CONCLUSÃO: existe uma relação entre as queixas de distúrbios alérgicos e/ou digestivos e a disfonia, uma vez que esses são co-fatores para o estabelecimento da disfonia e da lesão laríngea. A alta freqüência de queixas de distúrbios alérgicos nos indivíduos com disfonia organofuncional, no presente estudo, pode ter relação com o clima do sul do Brasil. PURPOSE: to check the occurrence of the complains of allergic and digestive disturbance in patients with organic-functional dysphonia that were attended in Speech and Language Therapist School Clinic. METHODS: this study is a sequence, retrospective, transverse study. We have done an analysis of 113 patients' medical records with organic-functional dysphonia that had complains of allergic and/or digestive disturbance, from 05 to 76-years-old, 41 male and 72 female. The hypothesis test for 2 proportions was used for the statistic analysis of data. RESULTS: there was a significant relationship of complains on associated allergic and digestive disturbance in patients with organic-functional dysphonia among the complains of allergic disturbance, digestive disturbance, and of both associated, the ones of allergic disturbance were significantly more frequent in patients with Organic-functional dysphonia. CONCLUSION: there is a relationship among the complains of allergic and/or digestive disturbance and the Organic-functional dysphonia, once that they are co-factors for causing dysphonia and larynx lesions. The high frequency concerning complaints of allergic disturbances in people with organic-functional dysphonia in this study can be linked with the weather in the south of Brazil.